Use of standardized letters of recommendation for otolaryngology head and neck surgery residency and the impact of gender. (8th August 2017) - Friedman, Remy; Fang, Christina H.; Hasbun, Johann; Han, Helen; Mady, Leila J.; Eloy, Jean Anderson; Kalyoussef, Evelyne
Abstract : Objectives: To evaluate gender‐based differences in narrative letters of recommendation (NLORs) and standardized letters of recommendation (SLORs) submitted for applicants to an otolaryngology head and neck surgery (OHNS) residency program. Study Design: Retrospective review. Methods: Nine hundred fifty‐eight letters of recommendation (LORs) submitted to one OHNS program in 2013 to 2014 were analyzed. Results: NLORs (n = 590) and SLORs (n = 368) were reviewed. Male writers composed over 85% of all LORs. Compared with male writers, female writers of LORs were more likely to compose a letter of minimal assurance ( P < 0.025). Female writers of SLORs were more likely to rank applicants higher in communication skills ( P < 0.035) and match potential ( P < 0.045). Analysis of LORs by applicant gender revealed that female applicants were more likely than male applicants to be described as team players ( P < 0.025) and less likely to receive a letter of minimal assurance ( P < 0.001). Compared with SLORs, NLORs written for male applicants were more likely to reference their leadership potential ( P < 0.001). Female applicants were less likely to be described as "bright" ( P < 0.001) and more likely to have their appearance mentioned ( P < 0.03) in NLORs when compared to SLORs. Conclusion: Although we found that SLORs reduce gender biases compared to NLORs, there remain significant differences in how female and male applicants are described. Greater awareness of historical biases likely has contributed to more equitable letter writing, although impactful gender biases remain when reviewing applicants. Level of Evidence: NA. Laryngoscope, 127:2738–2745, 2017